Mitochondrial Dynamics: A Key Role in Neurodegeneration and a Potential Target for Neurodegenerative Disease - Yang, Danying; Ying, Jun; Wang, Xifeng; Zhao, Tiancheng; Yoon, Sungtae; Fang, Yang; Zheng, Qingcui; Liu, Xing; Yu, Wen; Hua, Fuzhou (Frontiers in Neuroscience, 2021)
Neurons are the most energy and oxygen-demanding cell types, thus require large amounts of energy. The energy of neurons is provided by mitochondria, which is a dynamic organelle, in a dynamic balance of division and fusion. Three major dynamic processes of mitochondria cooperate with each other and help neurons meet the challenges they face. (1) the transport of mitochondria in axons ensures the survival of nerve synapses, (2) mitophagy maintains mitochondrial quality control through various pathways, and (3) the fusion and division of mitochondria regulate the morphology of mitochondria. This review discussed the status and prospects of the dynamic mechanism of mitochondria and its influence on several neurodegenerative diseases—Alzheimer’s diseases, Parkinson’s diseases and Huntington’s diseases. The types of mitochondrial dynamics described include mitochondrial fission and fusion, mitophagy and mitochondrial transport within neuronal axon.